2022
DOI: 10.3897/pharmacia.69.e82097
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-FLD analysis of amino acids content in Chrysanthemum morifolium

Abstract: Chrysanthemum morifolium (Asteraceae family) have long been used as a tonic, antioxidant, antipyretic, analgesic, sedative, antitumor, neuroprotector, hepatoprotector and cardioprotector agent. This species should be reconsidered as possible sources of many biocompounds, especially amino acids. Thus, the aim of this study was to validate the chromatographic method for detection of amino acids and their identification in flowers and leaves of Ch. morifolium of variant Pectoral. HPLC-FLD method was evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Spirulina sample was then maintained for 24 h in the oven at 105 °C to facilitate the hydrolysis of AA chains, including peptides and protein into individual amino acids. Eventually, 6 ml NaOH (6 N) was added to 2 ml of the hydrolyzed HCl sample [ 28 ]. The resulting extracts underwent centrifugation at 3500 rpm and 1 ml of supernatants were evaporated using a rotary evaporator, with 3 washes performed using distilled water to remove residual HCl [ 29 ].…”
Section: Materiel and Methodsmentioning
confidence: 99%
“…Spirulina sample was then maintained for 24 h in the oven at 105 °C to facilitate the hydrolysis of AA chains, including peptides and protein into individual amino acids. Eventually, 6 ml NaOH (6 N) was added to 2 ml of the hydrolyzed HCl sample [ 28 ]. The resulting extracts underwent centrifugation at 3500 rpm and 1 ml of supernatants were evaporated using a rotary evaporator, with 3 washes performed using distilled water to remove residual HCl [ 29 ].…”
Section: Materiel and Methodsmentioning
confidence: 99%
“…Using HPLC-FLD assay, a total of fifteen amino acids after hydrolysis and ten amino acids in free form were identified in C. morifolium flowers, involving l -aspartic acid, l -serine, l -glutamic acid, l -histidine glycine, l -threonine, l -arginine, l -alanine, l -tyrosine, l -valine, l -phenylalanine l -isoleucine, l -lysine l -leucine and l -proline. Besides, other essential amino acids, l -lysine was found in higher amount 12.05 ± 0.02 μg/mg [ 25 ]. A recent study found that C. morifolium flower extract (CME) shows 1.96 nmol/mg protein in 0.2% CME samples [ 30 ].…”
Section: Nutritional Profilementioning
confidence: 99%
“…11,12 Therefore, accurate, simple, and fast methods are desired for determining Cys and Trp in many fields, such as food processing, biotechnology, and pharmaceutical industries. [13][14][15][16] Numerous analytical methods have been developed for amino acid quantification, e.g., high-performance liquid chromatography (HPLC), 17,18 spectrophotometry, 19 gas chromatography-mass spectroscopy (GC-MS), 20 and electrochemistry. 1,4,16 Among these methods, electrochemical procedures have attracted considerable interest in electro-active compounds because of their simplicity, low-cost, high sensitivity, and ease of miniaturization.…”
Section: Introductionmentioning
confidence: 99%